Perbedaan Metode Ijtihad Nahdlatul Ulama dan Muhammadiyah dalam Corak Fikih di Indonesia - Isa Ansori (Postgraduate State Islamic Institute (IAIN) Metro, 2014)
There were different orientation in the background and methods of ijthad between Bahtsul Masail Nahdlatul Ulama (NU) and Majelis Tarjih Muhammadiyah (The Muhammadiyah Legal Affairs Committee). The ijtihad orientation of Bahtsul Masail emphasizes on cultural approach to maintain the previous values that have been good, and take the new values better. This approach accepts local culture and wisdom as part of the past products that has no conflict with al-Qur’an and al-Hadith, or by changing the content of culture and local wisdom with Quranic and Sunnah content. This approach is different from the ijtihad orientation model developed by Majelis Tarjih Muhammadiyah called